Electrochemical device and electronic device

By using isolation films of aluminum atoms and fluorine atoms in the electrochemical device, combined with nitrile additives and propylene carbonate electrolyte, the problem of insufficient performance of the electrochemical device under high and low temperature conditions is solved, and higher puncture resistance, thermal safety performance and structural stability are achieved.

CN119674446APending Publication Date: 2025-03-21NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411793058.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

It is difficult for existing electrochemical devices to have excellent electrochemical performance and puncture resistance under high temperature conditions and low temperature conditions, and there are problems such as short circuit risk and insufficient thermal safety performance.

Method used

An electrochemical device is used, which includes a positive electrode sheet, a negative electrode sheet and a barrier film having aluminum atoms and fluorine atoms. The atomic percentage ratio of aluminum atoms and fluorine atoms in the isolation film is within the range of 1≤A≤4, the atomic percentage X% of aluminum atoms is 17≤X≤28, and the atomic percentage Y% of fluorine atoms is 7≤Y≤21. The electrolyte contains nitrile additives and propylene carbonate, which further optimizes the composition of the isolation film and electrolyte to improve performance.

Benefits of technology

This design significantly improves the puncture resistance of the isolation membrane, reduces the risk of short circuit in the electrochemical device, improves thermal safety performance and high-temperature circulation performance, and improves the structural stability and overcharge resistance of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005176453980000181
    Figure BDA0005176453980000181
  • Figure BDA0005176453980000191
    Figure BDA0005176453980000191
  • Figure BDA0005176453980000201
    Figure BDA0005176453980000201
Patent Text Reader

Abstract

The invention provides an electrochemical device and an electronic device, the electrochemical device comprises a positive pole piece, a negative pole piece and an isolating membrane, the isolating membrane is arranged between the positive pole piece and the negative pole piece, the isolating membrane has aluminum atoms and fluorine atoms, and the aluminum atoms and the fluorine atoms are in a 2 [mu] m * 2 [mu] m area of a scanning electron microscope picture of the isolating membrane. The ratio A of the atomic percent of the aluminum atoms to the atomic percent of the fluorine atoms is larger than or equal to 1 and smaller than or equal to 4, the atomic percent X% of the aluminum atoms is larger than or equal to 17 and smaller than or equal to 28, the atomic percent Y% of the fluorine atoms is larger than or equal to 7 and smaller than or equal to 21, and the electrolyte contains nitrile additives and propylene carbonate. According to the electrochemical device provided by the invention, the high-temperature cycle performance, the low-temperature intermittent cycle performance and the thermal safety performance of the electrochemical device can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with application number 202411188012.1, application date August 28, 2024, and invention name “A kind of isolation membrane, electrochemical device and electronic device”. Technical Field

[0002] The present application relates to the field of electrochemical energy storage, and in particular to an electrochemical device and an electronic device. Background Art

[0003] With the development of science and technology, electrochemical devices are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, special equipment, special aerospace and other fields. At present, there are more demands for the application scenarios of electrochemical devices. For example, under high temperature and low temperature conditions, the electrochemical device itself needs to have a certain puncture resistance and excellent electrochemical performance. Summary of the invention

[0004] The present application provides an electrochemical device and an electronic device.

[0005] In a first aspect, the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the separator has aluminum atoms and fluorine atoms. In a 2μm×2μm area of ​​a scanning electron microscope photograph of the separator, the ratio A of the atomic percentages of aluminum atoms and fluorine atoms satisfies: 1≤A≤4, wherein the atomic percentage X% of aluminum atoms satisfies: 17≤X≤28, and the atomic percentage Y% of fluorine atoms satisfies: 7≤Y≤21. The electrochemical device also includes an electrolyte, and the electrolyte contains a nitrile additive and propylene carbonate.

[0006] In the separator provided in the present application, the surface of the separator has aluminum atoms and fluorine atoms in a suitable atomic ratio, which can effectively improve the puncture resistance of the separator at 35°C. When the aluminum atom content is too high, there is a risk of the separator itself being punctured when the ratio A is large. Therefore, the separator that meets the atomic types and ratios in this range can effectively reduce the short-circuit risk of the electrochemical device. At the same time, when the fluorine atoms and aluminum atoms on the separator meet this range, the surface of the separator can play a certain protective role, which can improve the thermal safety performance of the electrochemical device. At the same time, the fluorine atoms can effectively improve the affinity between the surface of the separator and the electrolyte, which is more conducive to improving the liquid retention capacity of the electrochemical device during the cycle, thereby improving the high-temperature cycle performance of the electrochemical device. When the atomic percentage of aluminum atoms and fluorine atoms is within the above range, the anti-overcharge performance of the electrochemical device can also be improved, thereby improving the safety performance of the electrochemical device. When the atomic ratio of aluminum atoms or fluorine atoms is controlled within the above range, it is beneficial to keep the separator at a certain structural strength, which can effectively improve the puncture resistance at 35°C, reduce the short-circuit risk of the electrochemical device, and help improve the structural stability of the electrochemical device. If the atomic percentage of aluminum atoms is high, it will affect the transmission of lithium ions in the electrochemical device and affect the high-temperature cycle performance of the electrochemical device. If the atomic percentage of fluorine atoms is controlled within the above range, it can effectively improve the affinity between the isolation membrane and the electrolyte, and is more conducive to improving the liquid retention capacity of the electrochemical device during high-temperature cycles, thereby further improving the high-temperature cycle performance of the electrochemical device. In combination with the electrolyte containing nitrile additives and propylene carbonate, it is beneficial to reduce the generation of by-products in the electrolyte, which can further improve the DC impedance at high and low temperatures, reduce the amount of gas generated by the electrochemical device at high temperatures, reduce the overall expansion of the electrochemical device, and further improve the thermal safety performance of the electrochemical device.

[0007] Based on the first aspect, in some embodiments, the ratio E of the mass of the nitrile additive to the mass of propylene carbonate PC satisfies: 1≤E≤5. The nitrile additive includes succinonitrile, adiponitrile, acetonitrile, and ethylene glycol diethyl cyanide. When the electrolyte meets the range required by the present application, it is beneficial to reduce the generation of by-products in the electrolyte, further improve the DC impedance at high and low temperatures, reduce the amount of gas generated by the electrochemical device at high temperature, reduce the overall expansion of the electrochemical device, and improve the thermal safety performance of the electrochemical device.

[0008] Based on the first aspect, in some embodiments, the separator includes a substrate, the surface of the substrate has a coating, the coating includes a plurality of stripes arranged at intervals, the average spacing between two adjacent stripes is 1mm to 3mm, and the aluminum atoms and fluorine atoms are selected from boehmite and polyvinylidene fluoride on the stripes, respectively. The average spacing in this application refers to the average spacing obtained by taking the average of the spacings of 5 groups of different stripe groups as the straight-line distance between the center points of two adjacent stripes (referred to as a stripe group) in the width direction of the separator. Combined with the design of the coating including stripes, the liquid storage capacity of the electrochemical device can be further effectively improved, thereby further improving the low-temperature intermittent cycle performance of the electrochemical device. When the average spacing between two adjacent stripes is within a suitable range, it is beneficial to increase the interfacial bonding force between the separator and the positive and negative pole pieces, thereby further improving the low-temperature intermittent cycle performance of the electrochemical device, the high-temperature cycle performance, and improving the anti-overcharge performance of the electrochemical device at high temperatures.

[0009] Based on the first aspect, in some embodiments, the electrolyte further includes biphenyl, the mass of biphenyl in the electrolyte accounts for y% of the total mass of the electrolyte, 0.4≤y≤1.8, which can inhibit the preferential oxidation and decomposition of the carbonate electrolyte and inhibit the generation of gas at the interface. When the electrolyte contains both biphenyl and triphenylphosphine oxide, the two jointly participate in the formation of a solid electrolyte interface film, and the thickness of the formed solid electrolyte interface film at the interface is 100μm to 400μm, which can further inhibit the occurrence of side reactions at the interface, reduce the amount of gas generated at the interface, and further improve the thermal safety performance of the electrochemical device.

[0010] Based on the first aspect, in some embodiments, 2≤A≤3. The separator satisfying the above conditions can further improve the puncture resistance of the separator at 35°C, further reduce the short circuit risk of the electrochemical device, and improve the thermal safety performance of the electrochemical device.

[0011] Based on the first aspect, in some embodiments, the average spacing of the stripes on the separator of the present application is 1.2 μm to 2.5 mm. The separator meeting the above conditions can further improve the liquid storage capacity of the electrochemical device, and at the same time can further improve the transmission rate of lithium ions, and improve the low-temperature intermittent cycle performance and overcharge prevention performance of the electrochemical device.

[0012] Based on the first aspect, in some embodiments, the thickness of the stripes on the isolation membrane is 0.5 μm to 2 μm. The isolation membrane meeting the above conditions can further improve the high temperature cycle performance and overcharge prevention performance of the electrochemical device.

[0013] Based on the first aspect, in some embodiments, within a 1 mm×1 mm area, the coverage of the coating on the substrate surface is 15% to 25%. When the above range is met, the coating can effectively improve the liquid storage capacity of the electrochemical device, thereby improving the high temperature cycle performance and low temperature intermittent cycle performance of the electrochemical device.

[0014] Based on the first aspect, in some embodiments, at 35° C., the ratio B of the puncture force of the separator to the puncture force of the substrate satisfies: 1.1≤B≤2.0. This is beneficial to improving the overall mechanical properties of the separator, improving the high-temperature cycle performance and low-temperature intermittent cycle performance of the separator, and the anti-overcharge performance of the electrochemical device at high temperature.

[0015] Based on the first aspect, in some embodiments, the positive electrode plate includes a positive electrode material, and at 40°C, the dry pressing bonding force F between the coating and the positive electrode material satisfies: 2N / m≤F≤6.5N / m. It is beneficial to improve the bonding strength between the coating and the positive electrode material, and to improve the thermal safety performance of the electrochemical device. When the bonding strength is too high, it is not conducive to the transmission of active ions. When the bonding strength is too low, it will affect the overall structural stability and energy density of the electrochemical device, and easily lead to the occurrence of interfacial side reactions, thereby generating more gas. Therefore, satisfying the appropriate dry pressing bonding force of the present application is beneficial to improving the thermal safety performance of the electrochemical device, while alleviating the gas production behavior of the interface and reducing the amount of interfacial gas generated.

[0016] Based on the first aspect, in some embodiments, the positive electrode plate includes a positive electrode material, and the ratio D of Dv50 / Dn 10 of the positive electrode material satisfies: 20≤D≤45, which is beneficial to reduce the possibility of the positive electrode material puncturing the isolation membrane, thereby reducing the risk of short circuit in the electrochemical device, and improving the thermal safety performance of the electrochemical device at high temperature. By controlling the particle size range of the positive electrode material to control its specific surface area, it is possible to reduce the occurrence of side reactions and alleviate interfacial gas production behavior.

[0017] Based on the first aspect, in some embodiments, the ratio E of the mass of the nitrile additive to the mass of the organic solvent PC satisfies: 1≤E≤3. This is beneficial to further reduce the DC impedance at high and low temperatures, reduce the amount of gas generated by the electrochemical device at high temperatures, reduce the overall expansion of the electrochemical device during charging and discharging, and improve the thermal safety performance of the electrochemical device.

[0018] Based on the first aspect, in some embodiments, the electrolyte further includes triphenylphosphine oxide, and the mass of triphenylphosphine oxide accounts for x% of the total mass of the electrolyte, 0≤x≤4.5. When the mass proportion of triphenylphosphine oxide in the electrolyte is within the above range, triphenylphosphine oxide will participate in the formation of a solid electrolyte interface film with uniform thickness and denseness at the interface between the cathode and the electrolyte after the electrochemical device circulates 5 times. The thickness of the solid electrolyte interface film is 10μm to 150μm, and the interface film can participate in capturing gas molecules such as HF at the interface, thereby reducing the gas production at the interface in the electrochemical device. At the same time, the interface film can improve the interface stability of the positive electrode material, thereby improving the thermal safety performance of the electrochemical device.

[0019] A second aspect of the present application provides an electronic device, comprising the above-mentioned electrochemical device.

[0020] The isolation membrane provided in the present application has excellent structural strength and stability, and can improve the thermal safety performance of the electrochemical device. At the same time, combined with its own design of a coating with multiple stripes, it can improve the high-temperature cycle performance of the electrochemical device, improve lithium precipitation, and improve the low-temperature intermittent cycle performance and thermal safety performance of the electrochemical device. DETAILED DESCRIPTION

[0021] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0022] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.

[0023] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0024] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0025] The present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, the separator has aluminum atoms and fluorine atoms, and within a 2μm×2μm area of ​​a scanning electron microscope photograph of the separator, a ratio A of the atomic percentages of aluminum atoms and fluorine atoms satisfies: 1≤A≤4, wherein the atomic percentage X% of aluminum atoms satisfies: 17≤X≤28, and the atomic percentage Y% of fluorine atoms satisfies: 7≤Y≤21, and the electrochemical device further comprises an electrolyte, wherein the electrolyte contains a nitrile additive and propylene carbonate (PC).

[0026] In the present application, the surface of the isolating membrane that meets the above conditions has aluminum atoms and fluorine atoms in a suitable atomic ratio, which is beneficial to improve the structural strength of the isolating membrane, improve the puncture resistance of the isolating membrane at 35°C, and effectively reduce the short circuit risk of the electrochemical device. At the same time, when the ratio of the atomic percentage of fluorine atoms to aluminum atoms on the isolating membrane meets this range, the aluminum atoms and fluorine atoms can play a certain protective role on the surface of the isolating membrane, which can improve the thermal safety performance of the electrochemical device. At the same time, the isolating membrane containing fluorine atoms can also effectively improve the affinity between the isolating membrane and the electrolyte, which is more conducive to improving the liquid retention capacity of the electrochemical device during the cycle, thereby improving the high-temperature cycle performance of the electrochemical device. When the atomic percentage of aluminum atoms and fluorine atoms in the isolating membrane is within the above range, the isolating membrane also maintains the overall structural stability and structural strength, which is beneficial to reduce the shrinkage of the isolating membrane at high temperatures. The gas molecules generated by overcharging of the electrochemical device will be evenly distributed in the entire structure of the isolating membrane, and will not be excessively accumulated locally, thereby improving the anti-overcharge performance of the electrochemical device, and then improving the safety performance of the electrochemical device. In combination with the electrolyte containing nitrile additives and propylene carbonate, it is beneficial to reduce the generation of by-products in the electrolyte, which can further improve the DC impedance at high and low temperatures, reduce the amount of gas generated by the electrochemical device at high temperatures, reduce the overall expansion of the electrochemical device, and further improve the thermal safety performance of the electrochemical device.

[0027] If the ratio A of the atomic percentage of aluminum atoms to fluorine atoms is small, such as less than 1, the atomic percentage of aluminum atoms is small, which may affect the thermal safety performance and high temperature cycle performance of the isolation membrane; if the ratio A of the atomic percentage of aluminum atoms to fluorine atoms is large, such as greater than 4, when the atomic percentage of aluminum atoms is too high, the risk of puncturing the isolation membrane itself is increased, and the risk of short circuit of the electrochemical device is increased. In some embodiments, for example, A can be 1, 1.1, 1.3, 1.5, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.3, 3.5, 3.7, 3.8, 3.9, 4 or a range consisting of any two of the values.

[0028] In some embodiments, the atomic percentage ratio of aluminum atoms to fluorine atoms satisfies: 2≤A≤3. The puncture resistance of the separator at 35°C is further improved, the short circuit risk of the electrochemical device is further reduced, and the thermal safety performance of the electrochemical device is improved.

[0029] In some embodiments, X can be 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28 or a range consisting of any two of the values. Or Y can be 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 or a range consisting of any two of the values. The atomic percentage of aluminum atoms is controlled within the above range, so that the isolation membrane maintains a certain structural strength, which can effectively improve the puncture resistance at 35°C, reduce the short circuit risk of the electrochemical device, and help improve the structural stability of the electrochemical device. If the atomic percentage of aluminum atoms is large, it will affect the transmission of lithium ions in the electrochemical device and affect the high temperature cycle performance of the electrochemical device. The atomic percentage of fluorine atoms is controlled within the above range, which can effectively improve the affinity between the isolation membrane and the electrolyte, and is more conducive to improving the liquid retention capacity of the electrochemical device during the high temperature cycle, thereby further improving the high temperature cycle performance of the electrochemical device.

[0030] In some embodiments, the ratio E of the mass of the nitrile additive to the mass of propylene carbonate PC satisfies: 1≤E≤5. Nitrile additives include succinonitrile, adiponitrile, acetonitrile, and ethylene glycol diethyl cyanide. When the electrolyte meets the range required by the present application, it is beneficial to reduce the generation of by-products in the electrolyte, and can further improve the DC impedance at high and low temperatures, and reduce the amount of gas generated by the electrochemical device at high temperatures, reduce the overall expansion of the electrochemical device, and improve the thermal safety performance of the electrochemical device. For example, the ratio E can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, or a range consisting of any two of the values. When the electrolyte meets the range required by the present application, it is beneficial to reduce the generation of by-products in the electrolyte, and can further improve the DC impedance of the electrochemical device at high and low temperatures, improve the high temperature cycle performance and low temperature intermittent cycle performance of the electrochemical device, and reduce the amount of gas generated by the electrochemical device at high temperatures, and reduce the overall expansion of the electrochemical device. Further, the mass ratio E of the nitrile additive to the mass of propylene carbonate satisfies: 1≤E≤3. When the electrolyte meets the further preferred range of the present application, it can further reduce the gas generation of the electrochemical device at high temperature, reduce the overall expansion of the electrochemical device, and improve the thermal safety performance of the electrochemical device (such as the hot box test pass rate).

[0031] In some embodiments, the separator includes a substrate, the surface of the substrate has a coating, the coating includes a plurality of stripes arranged at intervals, the average spacing between two adjacent stripes is 1 mm to 3 mm, and the aluminum atoms and fluorine atoms are selected from boehmite and polyvinylidene fluoride on the stripes, respectively. The average spacing in this application refers to the average spacing obtained by taking the average of the spacings of 5 groups of different stripe groups as the straight-line distance between the center points of two adjacent stripes (referred to as a stripe group) in the width direction of the separator. The present application is combined with the design of containing multiple stripes in the coating, which can further effectively improve the liquid storage capacity of the electrochemical device, thereby facilitating further improvement of the low-temperature intermittent cycle performance and high-temperature cycle performance of the electrochemical device. And making the average spacing between two adjacent stripes within the above range is conducive to increasing the interfacial bonding force between the separator and the positive and negative pole pieces, thereby facilitating further improvement of the low-temperature intermittent cycle performance and high-temperature cycle performance and high-temperature anti-overcharge performance of the electrochemical device.

[0032] If the average spacing between two adjacent stripes is small, such as less than 1 mm, the number of stripes in the coating will increase, which may reduce the liquid storage capacity of the coating and affect the low-temperature intermittent cycle performance of the electrochemical device; if the average spacing between two adjacent stripes is large, such as greater than 3 mm, it may affect the adhesion between the coating and the electrode, thereby affecting the high-temperature cycle performance of the electrochemical device. In some embodiments, the average spacing can be 1 mm, 1.1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 3.0 mm, or a range consisting of any two of these values.

[0033] In some embodiments, the electrolyte further comprises biphenyl, the mass of biphenyl accounts for y% of the total mass of the electrolyte, 0.4≤y≤1.8. When the electrolyte comprises biphenyl and the mass proportion of biphenyl is within the above range, the preferential oxidation decomposition of the carbonate electrolyte can be suppressed, and the generation of gas at the interface can be reduced. When biphenyl and triphenylphosphine oxide are simultaneously contained in the electrolyte, the two jointly participate in the formation of a solid electrolyte interface film, and the thickness of the formed solid electrolyte interface film at the interface is 100μm to 400μm, which can further suppress the occurrence of side reactions at the interface, reduce the amount of gas generated at the interface, and further improve the thermal safety performance of the electrochemical device. In some embodiments, the mass of biphenyl accounts for y% of the total mass of the electrolyte, and y can be 0.4, 0.8, 1, 1.2, 1.5, 1.8 or a range consisting of any two values ​​therein.

[0034] In some embodiments, the average spacing between two adjacent stripes is 1.2 mm to 2.5 mm. The separator that meets the above conditions can further improve the liquid storage capacity of the electrochemical device, and at the same time can further improve the transmission rate of lithium ions, and improve the low-temperature intermittent cycle performance and anti-overcharge performance of the electrochemical device. In some embodiments, the average spacing between two adjacent stripes can be 1.2 mm, 1.5 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.2 mm, 2.4 mm, 2.5 mm or a range consisting of any two of these values.

[0035] In some embodiments, the thickness of the stripes is 0.5 μm to 2 μm, which can further improve the low-temperature intermittent cycle performance and overcharge prevention performance of the electrochemical device. In some embodiments, the thickness of the stripes can be 0.5 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.2 μm, 1.5 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, or a range consisting of any two of these values.

[0036] In some embodiments, in an area of ​​1 mm×1 mm, the coverage of the coating on the surface of the substrate is 15% to 25%. For example, the coverage of the coating on the surface of the substrate can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, or a range consisting of any two values ​​therein. When the above range is met, the coating can effectively improve the liquid storage capacity of the electrochemical device, and also facilitate the transmission of the electrolyte, improve the ionic conductivity of lithium ions, thereby improving the high temperature cycle performance and low temperature intermittent cycle performance of the electrochemical device.

[0037] In some embodiments, the isolation membrane of the present application includes a substrate, and at 35°C, the ratio B of the puncture force of the isolation membrane to the puncture force of the substrate satisfies: 1.1≤B≤2.0. For example, B can be 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or a range consisting of any two values ​​therein. When the puncture force of the isolation membrane and the puncture force of the substrate satisfy the above ratio range, it is beneficial for the isolation membrane to maintain a certain structural strength and improve the heat resistance of the isolation membrane as a whole, and improve the low-temperature intermittent cycle performance of the electrochemical device, as well as the high-temperature cycle performance and high-temperature overcharge prevention performance of the electrochemical device.

[0038] In some embodiments, the positive electrode sheet includes a positive electrode material, and at 40°C, the dry pressing bonding force F between the coating and the positive electrode material satisfies: 2N / m≤F≤6.5N / m. When the dry pressing bonding force between the coating and the positive electrode material meets the above range, the coating and the positive electrode material have a suitable bonding strength as a whole, which is conducive to the transmission of the electrolyte and is conducive to improving the interfacial bonding force of the electrochemical device, thereby improving the energy density and thermal safety performance of the electrochemical device; at the same time, within the above range, it is also conducive to improving the lithium precipitation phenomenon. When the dry pressing bonding force is large, it is not conducive to the transmission of lithium ions, and when the dry pressing bonding force is small, it will have an adverse effect on the overall structural stability and energy density of the electrochemical device. Therefore, meeting the appropriate dry pressing bonding force of the present application is conducive to improving the low-temperature intermittent cycle performance of the electrochemical device, and is also conducive to reducing the lithium precipitation of the interface. For example, F can be 2N / m, 2.5N / m, 3N / m, 4N / m, 5N / m, 6N / m, 6.5N / m or a range consisting of any two values ​​therein.

[0039] In some embodiments, the positive electrode sheet includes a positive electrode material, and the ratio D of Dv50 / Dn10 of the positive electrode material satisfies: 20≤D≤45, for example, D can be 20, 22, 24, 26, 27, 28, 29, 32, 33, 36, 38, 40, 41, 42, 44, 45 or a range consisting of any two values ​​therein. When the ratio D of Dv50 / Dn10 of the positive electrode material satisfies the above range, the risk of short circuit of the electrochemical device can be reduced by reducing the possibility of the positive electrode material puncturing the separator, thereby improving the thermal safety performance of the electrochemical device, and further improving the low-temperature intermittent cycle performance of the electrochemical device. And by controlling the particle size range of the positive electrode material to control its specific surface area, the occurrence of side reactions can be reduced, and the gas generation behavior of the interface of the electrochemical device can be alleviated. Wherein, Dn10 represents the particle size distribution based on the number, starting from the small particle size side, reaching the particle size of 10% of the cumulative number. Dv50 represents the particle size at which the volume accumulation of particles from the smaller particle size side reaches 50% in the volume-based particle size distribution.

[0040] In some embodiments, the electrolyte further comprises triphenylphosphine oxide, and the mass of triphenylphosphine oxide accounts for x% of the total mass of the electrolyte, and 0<x≤4.5. When the electrolyte contains triphenylphosphine oxide and the mass content of triphenylphosphine oxide is controlled within the above range, triphenylphosphine oxide will participate in the formation of a uniform and dense solid electrolyte interface film at the interface between the cathode and the electrolyte after the electrochemical device circulates 5 times. The thickness of the solid electrolyte interface film is 10μm to 150μm, and the interface film can participate in capturing gas molecules such as HF at the interface, thereby reducing the gas production at the interface in the electrochemical device. At the same time, the interface film can also improve the interfacial stability of the positive electrode material, thereby helping to improve the thermal safety performance of the electrochemical device. In some embodiments, the mass of triphenylphosphine oxide accounts for x% of the total mass of the electrolyte, and x can be 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or a range consisting of any two values ​​therein.

[0041] In the present application, the ratio A of the atomic percentage of aluminum atoms to fluorine atoms on the isolation film can be changed by adjusting the content of boehmite and polyvinylidene fluoride on the stripe coating on the isolation film base film. The base film in the present application is the substrate. The average spacing of the isolation film stripes and the thickness of the stripes can be changed by adjusting the parameters of the coating instrument (such as changing the width of the coating material on the base film, the thickness of the coating material on the base film).

[0042] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.

[0043] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material.

[0044] In some embodiments, the negative electrode plate may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may be disposed on one or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of a copper foil, a nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode active material layer may be coated only on a partial area of ​​the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0045] In some embodiments, as described above, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.

[0046] In some embodiments, the negative electrode active material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylate, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode active material layer may be made of any other suitable material. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder in the negative electrode active material layer may be (80-99): (0.5-10): (0.5-10), and it should be understood that this is only exemplary and not intended to limit the present application.

[0047] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer may include a positive active material (positive electrode material), and the positive active material layer may be located on one side or both sides of the positive current collector. In some embodiments, the positive current collector may be made of aluminum foil, and of course, other positive current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive current collector may be 1 μm to 200 μm. In some embodiments, the positive active material layer may be coated only on a partial area of ​​the positive current collector. In some embodiments, the thickness of the positive active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only, and other suitable thicknesses may be used.

[0048] In some embodiments, as described above, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the positive electrode active material may be doped and / or coated.

[0049] In some embodiments, the surface of the positive electrode material may include lithium phosphate and / or lithium niobate, the mass ratio of the two is 1:4-1:2, and the thickness of the covering layer is 3 μm-4 μm.

[0050] In some embodiments, the positive electrode active material layer also includes a positive electrode binder and a positive electrode conductor. In some embodiments, the positive electrode binder may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the positive electrode conductor may include at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes or carbon fibers.

[0051] In the present application, the electrochemical device includes an electrolyte, including a lithium salt and a non-aqueous solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include, but is not limited to, at least one of LiPF6, LiBF4, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalateborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt is 5% to 23%. For example, the concentration of the lithium salt in the electrolyte can be 5%, 8%, 12%, 16%, 20%, 23% or a range consisting of any two of the above values. The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, non-aqueous solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate may include but are not limited to at least one of ethylene carbonate (EC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC).

[0052] The fluorinated carbonate compound may include, but is not limited to, at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. Among them, the content of the non-aqueous solvent = 100% - the content of the lithium salt.

[0053] In some embodiments, the substrate includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. Especially polyethylene and polypropylene, they have a good effect on preventing short circuits and can improve the safety of the battery through the shutdown effect. In some embodiments, the thickness of the substrate is in the range of about 3 μm to 200 μm.

[0054] In some embodiments, the isolation membrane has a porous layer, and the binder of the porous layer is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece. The isolation membrane can also include a high melting point crystalline polymer or a high temperature resistant amorphous polymer, and the high temperature resistant resin includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene, polyvinylidene fluoride and cycloolefin copolymers. The high melting point crystalline polymer includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene or polyvinylidene fluoride, and the high temperature resistant amorphous polymer includes cycloolefin copolymers. Based on the mass of the polyolefin porous substrate, the mass percentage z of the high temperature resistant resin is 2% to 10%. For example, the mass percentage z of the high temperature resistant resin is 2%, 3%, 5%, 7%, 8%, 10% or a range consisting of any two of these values. When the above-mentioned type of high temperature resistant resin is added to the polyolefin porous substrate and the mass percentage of the high temperature resistant resin is controlled within the above range, it is beneficial to increase the melting point of the separator, improve the strength and high temperature performance of the electrochemical device.

[0055] In some embodiments, the electrochemical device is a lithium-ion battery, but the present application is not limited thereto.

[0056] In some embodiments of the present application, taking lithium-ion batteries as an example, the positive electrode sheet, the isolation membrane, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then placed in a shell such as an aluminum-plastic film for packaging, and the electrolyte is injected, formed, and packaged to make a lithium-ion battery.

[0057] The embodiment of the present application also provides an electronic device including the above-mentioned electrochemical device. The electrochemical device supplies power to the load of the electronic device. The above-mentioned electrochemical device includes a separator, and the electrochemical device including the separator has good high temperature cycle performance, low temperature intermittent cycle performance and thermal safety performance, thereby increasing the service life of the electronic device at high and low temperatures and the safety of use. The electronic device of the embodiment of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.

[0058] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0059] Preparation of lithium-ion batteries

[0060] <Comparative Example 1-1>

[0061] Isolation film:

[0062] Preparation of inorganic coating:

[0063] A polyethylene (PE) microporous membrane with a thickness of 8 μm was selected as the PE base membrane.

[0064] The inorganic particle boehmite with a Dv50 of 1.5 μm is mixed with polyacrylate and polyvinylidene fluoride in a mass ratio of 65:20:15 and dissolved in deionized water to form an inorganic coating slurry with a solid content of 35%. The obtained inorganic coating slurry is then evenly coated on both sides of the PE base film by a micro-concave coating method to obtain a heat-resistant layer, which is dried in an oven to obtain an inorganic coating with a thickness of 1.5 μm.

[0065] Organic coating preparation:

[0066] Add the first polymer polypropylene (PP) polymer particles based on propylene into a stirrer and stir evenly; add sodium carboxymethyl cellulose into a stirrer and stir evenly; add dimethyl siloxane, a wetting agent, into a stirrer, then add deionized water and stir, adjust the viscosity of the slurry to 30 mPa·s and the solid content to 7%, and obtain an organic coating slurry. The organic coating slurry is evenly coated on the inorganic coating on both sides of the base film, and after drying in an oven, a first coating is obtained. The thickness of the first coating is 0.6 μm. Then a certain amount of polyvinylidene fluoride PVDF is added to the first coating, so that the mass ratio of the first polymer, sodium carboxymethyl cellulose, dimethyl siloxane and polyvinylidene fluoride is 80:3.5:4.5:12, and after drying, a striped coating is obtained. Among them, the polymer is spherical or quasi-spherical in the isolation membrane, and the sphericity R of the polymer satisfies 0.8≤R≤1.0. The striped coating is prepared by gravure coating with a spacing of 1 μm and a thickness of 0.8 μm.

[0067] The rest of the preparation method and material selection of Comparative Example 1-1 are the same as those of Example 1-1.

[0068] <Example 1-1>

[0069] Positive electrode: lithium iron phosphate (Dv50 is 6μm, Dv 10 is 0.3μm), acetylene black and polyvinylidene fluoride are mixed in a weight ratio of 86:7:7 and added to N-methylpyrrolidone, and stirred into a uniform positive electrode slurry. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 85°C to obtain a positive electrode sheet coated with a positive electrode active material layer on one side. The above steps are repeated on the other side of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. After cold pressing, cutting and slitting, it is dried under vacuum conditions at 85°C for 4 hours, and then rolled and spot welded to obtain a positive electrode sheet with a specification of 74mm×867mm.

[0070] Negative electrode: artificial graphite, a negative electrode active material, conductive carbon black, styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) were mixed at a weight ratio of 97:1:1:1, deionized water was added, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry was 78wt%. The negative electrode slurry was evenly coated on one side of the negative electrode current collector copper foil, and dried at 115°C to obtain a negative electrode sheet coated with a negative electrode active material layer with a thickness of 85μm on one side, and the above steps were repeated on the other side of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 476mm×93.5mm was obtained.

[0071] Electrolyte: In a glove box filled with argon, first add 3.5% of succinonitrile and 85% of linear carbonate (the mass ratio of EP:EMC:DEC:PP is 15:20:20:45) accounting for the total mass content of the electrolyte, and then weigh 3.5% of propylene carbonate PC, 3% of triphenylphosphine oxide and 1.5% of biphenyl accounting for the total mass content of the electrolyte, and the rest are lithium salt lithium hexafluorophosphate.

[0072] Isolation film:

[0073] A polyethylene (PE) microporous membrane with a thickness of 8 μm was selected as the PE base membrane.

[0074] Preparation of inorganic coating:

[0075] The inorganic particle boehmite with a Dv50 of 1.5 μm is mixed with polyacrylate and polyvinylidene fluoride in a mass ratio of 85:10:5 and dissolved in deionized water to form an inorganic coating slurry with a solid content of 41%. The obtained inorganic coating slurry is then evenly coated on both sides of the PE base film by a micro-concave coating method to obtain a heat-resistant layer, which is dried in an oven to obtain an inorganic coating with a thickness of 1.5 μm.

[0076] Organic coating preparation:

[0077] Add the first polymer polypropylene (PP) polymer particles based on propylene monomer into a stirrer and stir evenly; add sodium carboxymethyl cellulose into the stirrer and stir evenly; add dimethyl siloxane, a wetting agent, into the stirrer, then add deionized water and stir, adjust the viscosity of the slurry to 30mPa·s and the solid content to 7%, and obtain an organic coating slurry. The organic coating slurry is evenly coated on the inorganic coating on both sides of the base film, and after drying in an oven, a first coating is obtained. The thickness of the first coating is 0.6μm. Then a certain amount of polyvinylidene fluoride PVDF is added to the first coating, so that the mass ratio of the first polymer, sodium carboxymethyl cellulose, dimethyl siloxane and polyvinylidene fluoride is 90:1.5:4.5:4, and after drying, a striped coating is obtained. Among them, the polymer is spherical or quasi-spherical in the isolation membrane, and the sphericity R of the polymer satisfies 0.8≤R≤1.0. The striped coating is prepared by gravure coating with a spacing of 1μm and a thickness of 0.8μm.

[0078] Preparation of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain an electrode assembly. After welding the pole ears, place the electrode assembly in an outer packaging aluminum-plastic film, remove moisture at 80°C, inject the above-mentioned electrolyte, and obtain a lithium-ion battery through vacuum packaging, standing, formation, shaping, capacity testing and other processes.

[0079] Lithium-ion battery performance test:

[0080] (1) Capacity retention rate of the 90th intermittent cycle test at -15℃:

[0081] At -15°C, the lithium-ion battery was allowed to stand for 30 minutes; it was charged to 3.8V at a constant current rate of 0.5C, and charged to 0.05C at a constant voltage rate at 3.8V; the battery was allowed to stand in a 45°C environment for 20 hours; the battery was cross-current discharged to 3.0V at a rate of 0.5C, and the battery discharge capacity was recorded; this was a complete intermittent charge and discharge cycle, and the battery was charged and discharged 90 times in the same way.

[0082] Capacity retention rate of lithium-ion battery after 90th cycle (%) = 90th cycle discharge capacity / first discharge capacity × 100%

[0083] (2) 138℃ hot box test pass rate:

[0084] The lithium-ion batteries in the embodiments and comparative examples were charged at room temperature at a constant current of 0.5C to a full charge voltage of 3.8V, and then continued to be charged at a constant voltage of 3.8V to a cut-off current of 0.05C to fully charge the batteries. The appearance was checked to ensure that the lithium-ion batteries were in a normal usable state. The fully charged batteries were placed in an oven and heated at a rate of 5°C / min until the specified hot box test temperature of 138°C was reached. The temperature was kept constant for one hour, and the battery status was observed during the process.

[0085] Judgment criteria: The battery does not catch fire or explode.

[0086] Hot box test pass rate = hot box test pass number / total number

[0087] (3) Battery 55℃ 600 cycles test:

[0088] The lithium ion batteries of the embodiments and comparative examples were repeatedly charged and discharged by the following steps, and the discharge capacity retention rate of the lithium ion batteries was calculated.

[0089] In an environment of 55°C, the first charge and discharge were carried out. Constant current charging was carried out at a charging current of 2C to a full charge voltage of 3.8V (4.5V is for the positive electrode as a ternary material. If the positive electrode material is lithium iron phosphate, the charging cut-off voltage is 3.8V, and if the positive electrode material is lithium cobalt oxide, the charging cut-off voltage is 4.2V), and then constant voltage charging was carried out at the maximum voltage until the current was 0.02C, and then constant current discharge was carried out at a discharge current of 0.5C until the final voltage was 3.0V, and the discharge capacity of the first cycle was recorded; then the above steps were repeated for 600 charge and discharge cycles, and the discharge capacity of the 600th cycle was recorded.

[0090] Cycle capacity retention rate=(discharge capacity at the 600th cycle / discharge capacity at the first cycle)×100%.

[0091] (4) 4C 4.5V 75℃ overcharge test:

[0092] For each embodiment and comparative example, 10 parallel sample lithium-ion batteries were discharged at 0.5C to 2.8V at 25°C, charged at 4C constant current to 4.5V at 75°C, and then charged at constant voltage for 3 hours, and the surface temperature change of the battery cell was monitored (the passing standard was that the battery cell did not catch fire, burn, or explode).

[0093] (5) Battery 55℃ gas generation test:

[0094] After constant current charging at a current value of 0.2C at 55°C until reaching 3.8V, constant voltage charging was performed at 3.8V for 1 hour. Then, the charged battery was stored in a constant temperature chamber at 55°C. After 200 hours, the battery was taken out of the constant temperature chamber, and after returning to room temperature, the gas generation of each battery was measured. This method was used to evaluate the 3.8V storage characteristics of the battery. The gas generation amount was measured using the following Archimedean method: a test battery was placed in a container filled with ultrapure water, and the volume of the single-layer laminated battery was measured by the weight change before and after. As a device for measuring volume by weight change, a densimeter MD S-300 manufactured by AlphaMirage Corp. was used.

[0095] Isolation film performance test:

[0096] (1) Atomic percentage test of aluminum atoms and fluorine atoms:

[0097] The isolation film samples were prepared and tested using a scanning electron microscope (SEM) and an energy dispersive spectrometer (EDS). Five 2μm×2μm areas were selected for EDS analysis. After the atomic percentages of aluminum atoms and fluorine atoms were obtained, the average values ​​of each of the aluminum atoms and fluorine atoms were calculated, thereby obtaining the ratio A of the atomic percentages of aluminum atoms and fluorine atoms.

[0098] (2) Test of average spacing of stripes:

[0099] The average stripe spacing is measured under an electron microscope or a scanning electron microscope. The specific method is to take the straight-line distance between the center points of two adjacent stripes (called a stripe group) along the width direction of the isolation film as the spacing, and take the average spacing of 5 different stripe groups to obtain the average spacing.

[0100] (3) Test of coating coverage on substrate surface:

[0101] Select a 1 μm×1 μm area under an electron microscope or a scanning electron microscope to calculate the ratio of the area of ​​the strip coating to the area of ​​the entire area (1 μm×1 μm). Three parallel samples can be selected and the average value is the coverage.

[0102] (4) Dry pressing adhesion test between coating and positive electrode:

[0103] The 180° peel test standard was used to test the dry pressing adhesion between the separator and the positive electrode. The separator and the positive electrode were cut into 54.2mm×72.5mm samples, and the separator and the positive electrode were compounded. The heat press was used at a temperature of 40°C and a pressure of 1Mpa for 100 seconds. The compounded samples were cut into 15mm×54.2mm strips and the adhesion was tested according to the 180° peel test standard. The adhesion between the coating and the positive electrode was tested separately.

[0104] (5) Particle size of positive electrode active material Dn 10, Dv50

[0105] Dn 10 represents the particle size at which the number of particles reaches 10% of the cumulative number from the small particle size side in the particle size distribution based on the number. Dv50 represents the particle size at which the volume of particles reaches 50% of the cumulative volume from the small particle size side in the particle size distribution based on the volume. The most common instrument used for detection is a laser particle size analyzer.

[0106] (6) Puncture force test of isolation film and substrate:

[0107] At 35°C, fix the isolation membrane flatly on the test fixture, and place the fixture vertically below the mobile bracket of the high-speed rail tensile machine; secondly, pierce the isolation membrane with a spherical steel needle with a diameter of 1.0mm at a speed of 300±10mm / min, and measure the force required for the steel needle to pierce the isolation membrane as the puncture force. Wash the coating on the isolation membrane, and then fix the isolation membrane with only the base membrane flatly on the test fixture, and place the fixture vertically below the mobile bracket of the high-speed rail tensile machine; secondly, pierce the isolation membrane with a spherical steel needle with a diameter of 1.0mm at a speed of 300±10mm / min, and measure the force required for the steel needle to pierce the base membrane as the puncture force.

[0108] Example 1-2 to Example 1-18

[0109] By adjusting the mass ratio and solid content of the inorganic particle boehmite and the polyacrylate and polyvinylidene fluoride in Example 1-1, as well as the mass ratio of the first polymer, sodium carboxymethyl cellulose, dimethylsiloxane and polyvinylidene fluoride in the organic coating, the corresponding aluminum atom and fluorine atom contents are adjusted; the average spacing between adjacent stripes, the thickness of the stripes and the coverage can all be adjusted by the gravure coating method to obtain the relevant parameters in Table 1, and the rest are the same as Example 1-1.

[0110] Comparative Examples 1-2 to Examples 1-4

[0111] The inorganic particles boehmite and polyacrylate and polyvinylidene fluoride were adjusted according to the mass ratio and solid content, as well as the mass ratio of the first polymer, sodium carboxymethyl cellulose and dimethylsiloxane in the organic coating, and the corresponding aluminum atom and fluorine atom contents were adjusted to obtain the relevant parameters adjusted in Table 1. The rest were the same as Example 1-1.

[0112] Example 2-1 to Example 2-22

[0113] The Dv50 and Dn10 of the positive electrode material can be obtained by ball milling and stirring. Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1.

[0114] Example 2-23 to Example 2-26

[0115] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1.

[0116] Table 1

[0117]

[0118] In the above Table 1, compared with Comparative Examples 1-1 and 1-2, in Examples 1-1 to 1-7, when the ratio of the atomic percentage of aluminum atoms to fluorine atoms is within a suitable range, the overall structural strength of the separator is improved, the affinity of the separator to the electrolyte is improved, and the degree of thermal shrinkage of the separator at high temperature is reduced, thereby improving the thermal safety performance, high temperature cycle performance and overcharge prevention performance of the lithium-ion battery. In particular, when the ratio of the atomic percentage of aluminum atoms to fluorine atoms is between 2 and 3, the thermal safety performance, high temperature cycle performance and overcharge prevention performance of the lithium-ion battery are further improved.

[0119] Compared with Comparative Examples 1-3 and 1-4, in Examples 1-1 and 1-8 to 1-12, when the average spacing of the stripes in the coating and the coverage of the coating are within a suitable range, the thermal safety performance, high temperature cycle performance and overcharge prevention performance of the lithium-ion battery can be improved.

[0120] In particular, in combination with Examples 1-13 to 1-18, when the thickness of the stripes in the coating is within a suitable range, the thermal safety performance, high temperature cycle performance and overcharge prevention performance of the lithium-ion battery can also be improved.

[0121] In particular, when the atomic percentage of aluminum atoms is within a suitable range, it is also beneficial to improve the high temperature cycle performance and overcharge prevention performance of the lithium ion battery. When the atomic percentage of fluorine atoms is within a suitable range, it is also beneficial to improve the thermal safety performance, high temperature cycle performance and overcharge prevention performance of the lithium ion battery.

[0122] Table 2

[0123]

[0124] In the above Table 2, in Example 1-1 and Examples 2-1 to 2-7, when the ratio D of the particle size Dv50 / Dn 10 of the positive electrode material is within an appropriate range, it is beneficial to improve the hot box test pass rate and low-temperature intermittent cycle performance of the lithium-ion battery, and has good thermal safety performance.

[0125] In particular, in Example 1-1 and Examples 2-8 to 2-12, when the ratio of the mass of succinonitrile to the mass of propylene carbonate in the electrolyte satisfies a certain range, the gas generation of the lithium-ion battery at high temperature is further reduced, and the low-temperature intermittent cycle performance and hot box pass test rate of the lithium-ion battery are improved.

[0126] In Example 2-13 to Example 2-22, the mass ratio of triphenylphosphine oxide and biphenyl in the electrolyte is adjusted. When the mass ratio of triphenylphosphine oxide and biphenyl is within an appropriate range, the gas production in the lithium-ion battery is reduced, and the lithium-ion battery has good low-temperature intermittent cycle performance and hot box pass test rate.

[0127] Table 3

[0128]

[0129] In the above Table 3, by selecting different components of nitrile additives in the electrolyte, the lithium-ion battery has less gas generation at 55°C and has good low-temperature intermittent cycle performance and hot box test pass rate.

[0130] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.

Claims

1. An electrochemical device, comprising a positive electrode sheet and a negative electrode sheet, characterized in that: The electrochemical device further includes a separator, which is disposed between the positive electrode plate and the negative electrode plate, and has aluminum atoms and fluorine atoms. In a 2 μm×2 μm region of a scanning electron microscope photograph of the separator, a ratio A of the atomic percentages of the aluminum atoms and the fluorine atoms satisfies: 1≤A≤4, wherein the atomic percentage X% of the aluminum atoms satisfies: 17≤X≤28, and the atomic percentage Y% of the fluorine atoms satisfies: 7≤Y≤21; The electrochemical device further comprises an electrolyte containing a nitrile additive and propylene carbonate.

2. The electrochemical device according to claim 1, characterized in that The ratio E of the mass of the nitrile additive to the mass of the propylene carbonate satisfies: 1≤E≤5, and the nitrile additive includes at least one of adiponitrile, succinonitrile, acetonitrile, and ethylene glycol diethyl cyanide.

3. The electrochemical device according to claim 1, characterized in that The isolation film includes a substrate, a surface of the substrate has a coating, the coating includes a plurality of stripes arranged at intervals, an average spacing between two adjacent stripes is 1 mm to 3 mm, and the aluminum atoms and the fluorine atoms are respectively selected from boehmite and polyvinylidene fluoride on the stripes.

4. The electrochemical device according to any one of claims 1 to 3, characterized in that The electrolyte further comprises biphenyl, the mass of the biphenyl accounts for y% of the total mass of the electrolyte, and 0.4≤y≤1.

8.

5. The electrochemical device according to any one of claims 1 to 3, characterized in that: 2≤A≤3。 6. The electrochemical device according to claim 3, characterized in that The isolation film also satisfies at least one of the following conditions: (1) The average distance between two adjacent stripes is 1.2 mm to 2.5 mm; (2) The thickness of the stripes is 0.5 μm to 2 μm.

7. The electrochemical device according to claim 3, characterized in that In an area of ​​1 mm×1 mm, the coverage of the coating on the surface of the substrate is 15% to 25%.

8. The electrochemical device according to claim 3, characterized in that At 35° C., a ratio B of the puncture force of the isolation film to the puncture force of the substrate satisfies: 1.1≤B≤2.

0.

9. The electrochemical device according to claim 3, characterized in that The positive electrode plate includes a positive electrode material, and at 40° C., a dry pressing bonding force F between the coating and the positive electrode material satisfies: 2N / m≤F≤6.5N / m.

10. The electrochemical device according to claim 1, characterized in that The positive electrode plate comprises a positive electrode material, and a ratio D of a particle size Dv50 / Dn 10 of the positive electrode material satisfies: 20≤D≤45.

11. The electrochemical device according to claim 2, characterized in that: 1≤E≤3。 12. The electrochemical device according to claim 1, characterized in that The electrolyte further comprises triphenylphosphine oxide, the mass of which accounts for x% of the total mass of the electrolyte, 0<x≤4.

5.

13. An electronic device, characterized in that: An electrochemical device comprising any one of claims 1 to 12.